Implications of nutritional status and immunonutrition in COVID-19: a narrative literary review (Research, Society and Development, 2022)
COVID-19 is a disease caused by a virus of the Coronaviridae family, characterized by respiratory symptoms that can be mild or severe, and can lead to respiratory failure and death. The immune system is the barrier that fights viral infections, and the impact of food on the development and maintenance of immune cells is proven in the literature. In the face of an infection, energy expenditure is increased, as well as the need for nutrients. In this way, nutritional status, diet and lifestyle are considered relevant, as they can affect the evolution and good prognosis of patients with COVID-19. The objective was to evaluate the influence of nutritional status and immunonutrition in the management of SARS-CoV-2 infection. This is a narrative review, in which topics on COVID-19, the immune system, viral infections and nutrients were studied. It was found that an adequate and healthy diet is essential for the functioning of the immune system to act against viral infections, including COVID-19. Research has shown that supplementing some micronutrients increases viral defense capacity, however more studies are needed to prove this hypothesis. Changes in nutritional status directly impact the course of the disease, aggravating the inflammatory process and increasing the risk of death. It is concluded that the adequacy of nutritional status, including a healthy diet, with adequate intake of macronutrients, vitamins and minerals, is very important to minimize the effects of COVID-19 on health.